Arabic, persian words in terminology of the social sciences - Zhiyekbayeva А. В. (Journal of Oriental Studies, 2016)
This article discusses the concept of social terminology and defi nitions of Social Sciences of the Kazakh language, derived fromborrowings from Arabic and Persian languages.